Effects of Agaricus blazei Murrill polysaccharides on hyperlipidemic rats by regulation of intestinal microflora. Issue 6 (19th April 2020) - Li, Yuxin; Lu, Xuechun; Li, Xiao; Guo, Xiao; Sheng, Yu; Li, Yingna; Xu, Guangyu; Han, Xiao; An, Liping; Du, Peige
Abstract: The present research envisaged the effects of Agaricus blazei Murrill polysaccharides (ABPs) on blood lipids and its role in regulation of the intestinal microflora in hyperlipidemic rats. The acidic polysaccharide fraction of Agaricus blazei Murrill was obtained by DEAE‐cellulose ion exchange column chromatography. The sugar content of ABP was 75.1%. Compared with the model group (MG), the serum TC, TG, and LDL‐C levels decreased ( p  < .05 or p  < .01) and the HDL‐C levels increased ( p  < .01) significantly in the ABP group. Expression of CYP7A1 was up‐regulated ( p  < .01), and that of SREBP‐1C ( p  < .05) was down‐regulated significantly in the liver tissue of rats in the ABP group. Additionally, the disordered hepatic lobules and the steatosis of hepatocytes were found to be significantly alleviated in the ABP group. We believe that ABP can reduce the ratio of Firmicutes/Bacteroidetes and reduce the relative abundance of Firmicutes, Ruminococcaceae_unclassified, and Ruminococcaceae, increasing the relative abundance of Proteobacteria, Clostridium_sensu_stricto, Allobaculum, Peptostreptococcaceae, Clostridiaceae_1, and Erysipelotrichaceae as targets to regulate blood lipids. The results showed ABP could regulate the dyslipidemia in rats with hyperlipidemia. The mechanism may be through the regulation of the imbalance of intestinal microflora induced by the high‐fat diet in rats, which may be one of the important ways of its intervention on the dyslipidemia induced by high‐fat diet. Abstract : Agaricus blazei Murrill polysaccharides (ABPs) could regulate the blood lipids in hyperlipidemic rats. The mechanism may be through the regulation of the imbalance of intestinal microflora induced by the high‐fat diet in rats, which may be one of the important ways of its intervention on the dyslipidemia induced by high‐fat diet.